Implemtasi Pembelajaran Kemuhammadiyahan di SMK Muhammadiyah Ngawen - Mohamad Saifula Yusuf; Romelah Romelah (Moral : Jurnal kajian Pendidikan Islam, 2025)
The holistic learning model in the Muhammadiyah subject at SMK Muhammadiyah Ngawen was developed to answer the challenges of education that tends to prioritize cognitive aspects without paying attention to the integration of spiritual, emotional, and social values. This study uses a literature study method with a qualitative approach to analyze the concept, stages, and implementation of the holistic learning model. The results of the study indicate that this model is able to integrate cognitive, affective, and psychomotor dimensions through contextual, experiential, and reflective approaches that are relevant to students' needs. The learning stages include self-understanding, relationship development, contextual learning, direct experience, reflection, implementation, and continuous development. This model also emphasizes collaboration with the Muhammadiyah community, utilization of technology, and strengthening the role of teachers as learning facilitators. Through a holistic approach, students not only understand Muhammadiyah values ​​theoretically but are also able to apply them in everyday life, form an Islamic character with integrity, and become agents of positive change in society. This study makes an important contribution to the development of holistic education in Islamic-based schools.